2015
DOI: 10.1523/eneuro.0078-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

DREADD-Induced Silencing of the Medial Olfactory Tubercle Disrupts the Preference of Female Mice for Opposite-Sex Chemosignals

Abstract: Attraction to opposite-sex pheromones during rodent courtship involves a pathway that includes inputs to the medial amygdala (Me) from the main and accessory olfactory bulbs, and projections from the Me to nuclei in the medial hypothalamus that control reproduction. However, the consideration of circuitry that attributes hedonic properties to opposite-sex odors has been lacking. The medial olfactory tubercle (mOT) has been implicated in the reinforcing effects of natural stimuli and drugs of abuse. We performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 55 publications
1
43
0
Order By: Relevance
“…Previous studies also reported that the preference to investigate urinary volatiles of male vs. estrous females was not reduced in female mice after surgical removal of the VNO (Keller et al ., ; Martel & Baum, ). The results of these latter studies along with those of the current experiment also contrast with our previous report (DiBenedictis et al ., ) that DREADD‐induced silencing of the mOT blocked the preference of estrous females to seek out both volatile and non‐volatile urinary chemosignals from testes‐intact males vs. estrous females. Presumably, volatile male pheromonal signals processed via the MOS lost their incentive value after silencing of the mOT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also reported that the preference to investigate urinary volatiles of male vs. estrous females was not reduced in female mice after surgical removal of the VNO (Keller et al ., ; Martel & Baum, ). The results of these latter studies along with those of the current experiment also contrast with our previous report (DiBenedictis et al ., ) that DREADD‐induced silencing of the mOT blocked the preference of estrous females to seek out both volatile and non‐volatile urinary chemosignals from testes‐intact males vs. estrous females. Presumably, volatile male pheromonal signals processed via the MOS lost their incentive value after silencing of the mOT.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, inputs from the basolateral amygdala, including the lateral nucleus, guide behaviors in response to conditioned social cues (Martinez et al, 2011;Takahashi et al, 2013), and inputs from olfactory regions guide social behaviors in response to pheromones and other odor cues (Kang et al, 2009;Samuelsen and Meredith, 2009a;DiBenedictis et al, 2015). Diminished responses to these inputs is expected to lead to reduced production of social behaviors (DiBenedictis et al, 2015;Noack et al, 2015). However, the outcome of these impairments on MeApd and MeApv is different, with a general decrease of responsiveness in MeApv but a more specific deficit in MeApd at higher frequency inputs.…”
Section: Discussionmentioning
confidence: 99%
“…49,58 In mice the PlCo responds to both attractive and aversive odors, 59 while ACo activation seems most selective for aversive odors. 49,58 In mice the PlCo responds to both attractive and aversive odors, 59 while ACo activation seems most selective for aversive odors.…”
Section: Organization Of the Main Olfactory System And Its Involvemmentioning
confidence: 99%
“…It therefore seems that the involvement of the Me in olfactory-mediated sexually dimorphic behaviors will depend largely upon activation of the AOS, which complicates an assessment of MOS involvement in pheromone signaling. 58,[99][100][101] Lesions or chemogenetic inactivation of the Me disrupts innate preferences for these odors in both sexes. [93][94][95][96] Of course, the Me is heterogeneous, consisting of posterior and anterior, as well as dorsal and ventral subdivisions that differ both structurally and functionally.…”
Section: Medial Amygdalamentioning
confidence: 99%